Ambrozjaster, Komentarz do Listu św. Pawła do Rzymian, tłum. Jan Sułowski, red. J. Żelazny, rewizja przekładu L. Biełas, S. Kalinkowski, J. Krykowski, H. Pietras, J. Woch, R. Zarzeczny, ŹMT 19, Kraków 2000, Wydawnictwo WAM, ss. 198 - Figiel, Józef (Vox Patrum, 2000)
review